2017
DOI: 10.1186/s12958-017-0231-z
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of hyperandrogenism and ovarian morphology changes as features of polycystic ovary syndrome: a systematic review

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disorder, affecting 9–18% of women in reproductive age that causes hyperandrogenism and infertility due to dysfunctional follicular maturation and anovulation. The etiology of PCOS is still poorly known, and information from experimental animal models may help improve current understanding of the mechanisms of PCOS initiation and development. Therefore, we conducted a systematic review of currently available methods for simulation of PCOS in experimental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 63 publications
2
64
0
1
Order By: Relevance
“…Thus, we hypothesize that prenatal androgen exposure may trigger ASD development. The DHT treatment was used to mimic PCOS conditions during the in vivo rat experiments (Mannerås et al, 2007;Noroozzadeh et al, 2017;Paixão et al, 2017). Our results show that prenatal DHT exposure induces ALB in offspring with suppressed expression of ERβ and SOD2 in the amygdala Li et al, 2018;Xie et al, 2018).…”
Section: Prenatal Dht Exposure-mediated Autism-like Behaviormentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, we hypothesize that prenatal androgen exposure may trigger ASD development. The DHT treatment was used to mimic PCOS conditions during the in vivo rat experiments (Mannerås et al, 2007;Noroozzadeh et al, 2017;Paixão et al, 2017). Our results show that prenatal DHT exposure induces ALB in offspring with suppressed expression of ERβ and SOD2 in the amygdala Li et al, 2018;Xie et al, 2018).…”
Section: Prenatal Dht Exposure-mediated Autism-like Behaviormentioning
confidence: 78%
“…Further investigation shows that DHT/BBR-mediated gene suppression is due to hypermethylation on the related gene promoters. We further established an in vivo PCOS rat model by DHT administration (Mannerås et al, 2007;Paixão et al, 2017) and found that maternal PCOS induces autism-like behavior (ALB) in offspring through ERβ/SOD2 suppression and subsequent oxidative stress and mitochondrial dysfunction. Prenatal treatment of AR knockdown restores this effect, indicating that prenatal DHT exposure induces ALB through the AR signaling pathway; interestingly, both prenatal and postnatal treatment of BBR partly restores this effect.…”
mentioning
confidence: 99%
“…1 Weight difference of animals before and after treatment in the groups (mean ± SEM). ++ P < 0.01 PCO and 100 mg/kg of extract versus control, * P < 0.05, extract versus PCO (2) polycystic ovary [2,4]. Therefore, biochemical markers and ovarian biopsy are usual evidence for PCOS diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, PCOS was described by Stein and Leventhal in the mid-1930s, but the exact cause of PCOS is unclear yet [3]. Both genetic and environmental factors (obesity and lack of physical exercise) can be significantly involved, and most treatments of PCOS are palliative which focuses on the symptoms of this disease and cannot completely cure PCOS [4].…”
Section: Introductionmentioning
confidence: 99%
“…Androgens are considered the main culprit of PCOS, and therefore the most common experimental model makes use of androgen administration to induce symptoms and alterations that represent a good paradigm of hyperandrogenism-dependent PCOSlike syndrome (Paixão, Ramos, Lavarda, Morsh, & Spritzer, 2017). An alternative experimental model for PCOS induction in rodents is provided by exposing them to a regimen of continuous light.…”
mentioning
confidence: 99%